800 horsemen God's history makers : Australia's place in Bible prophecy - Stringer, Col (Robina, QLD Col Stringer ministries, 1998)
Includes bibliographical references and photographs.
3rd reprinting
Keywords: Church history -- Australia; Military history -- religious aspects -- Christianity -- Australia